Foliar micromorphology in the classification of South American Hybanthus species (Violaceae) - Seo, Micaela Noemi (2011)
The infrageneric classification of Hybanthus subgen. Ionidium (Violaceae) is unclear and needs to be redefined. In the present study, it is proposed to be separated into five clearly distinct sections, based on the leaf micromorphology, according to the presence or absence of different trichomes and papillae. Scanning electron microscopy provided evidence supporting changes in the systematics of Hybanthus subgen. Ionidium. Five well-defined leaf micromorphological types were identified for the South American species studied. Additionally, three new sections are established in this study: Hybanthus sect. Ionidium, Hybanthus sect. Parviflorae and Hybanthus sect. Pombaliae. Hybanthus atropurpureus is designated as the lectotype of Hybanthus sect. Micranthae.